2022
DOI: 10.1097/pas.0000000000001987
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Inflammatory Myofibroblastic Tumors

Abstract: Inflammatory myofibroblastic tumor (IMT) of the uterus is a rare mesenchymal tumor with largely benign behavior; however, a small subset demonstrate aggressive behavior. While clinicopathologic features have been previously associated with aggressive behavior, these reports are based on small series, and these features are imperfect predictors of clinical behavior. IMTs are most commonly driven by ALK fusions, with additional pathogenic molecular alterations being reported only in rare examples of extrauterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…1,11 Nevertheless, additional genetic alterations, such as TP53 mutation or bi-allelic CDKN2A deletion, have been associated with aggressive behavior. [13][14][15] In conclusion, uterine IMTs are relatively uncommon, particularly in the absence of typical symptoms. As such, IMTs are frequently misdiagnosed or go unnoticed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11 Nevertheless, additional genetic alterations, such as TP53 mutation or bi-allelic CDKN2A deletion, have been associated with aggressive behavior. [13][14][15] In conclusion, uterine IMTs are relatively uncommon, particularly in the absence of typical symptoms. As such, IMTs are frequently misdiagnosed or go unnoticed.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 Nevertheless, additional genetic alterations, such as TP53 mutation or bi-allelic CDKN2A deletion, have been associated with aggressive behavior. 13-15…”
Section: Discussionmentioning
confidence: 99%
“…46 In the study by Ladwig et al, uterine IMTs with an indolent behaviour showed isolated ALK fusions, while aggressive uterine IMTs additionally harboured numerous mutations and deletions. 47 As the scope of this study was to detect the main molecular drivers of IMT, we did not perform DNA analysis on the ALK/ROS1 fusion-positive IMTs and therefore could not evaluate potential additional genetic alterations in the IMTs which might influence biological behaviour. However, as the vast majority of ALK fusion-positive IMTs (excluding EIMS) follow an indolent course, more research on kinase fusion-negative IMTs seems more urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…described two cases of recurrent IMT with a PIK3CA and KIT mutation, respectively, present in the recurrence, but not in the primary IMT 46 . In the study by Ladwig et al ., uterine IMTs with an indolent behaviour showed isolated ALK fusions, while aggressive uterine IMTs additionally harboured numerous mutations and deletions 47 . As the scope of this study was to detect the main molecular drivers of IMT, we did not perform DNA analysis on the ALK/ROS1 fusion‐positive IMTs and therefore could not evaluate potential additional genetic alterations in the IMTs which might influence biological behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular overlap may also be noted. Most IMTs are associated with ALK rearrangements, but other tyrosine kinase genes, such as ROS1 and RET, rearrangements can be the driver event (3,26). Interestingly, one of the ALK gene fusion partners described in IMT is EML4, and EML4::ALK rearrangements are frequent in non-small cell lung adenocarcinoma (27,28).…”
mentioning
confidence: 99%